Enhancing low‐temperature energy harvesting by lead‐free ferroelectric Ba(Zr0.1Ti0.9)O3. Issue 1 (24th July 2022) - Ngo, Nguyen Chi Trung; Sugiyama, Hironari; Sodige, Buddhika Amila Kumara; Wiff, Juan Paulo; Yamanaka, Satoru; Kim, Yoonho; Suzuki, Tsuneo; Baba, Masaaki; Takeda, Masatoshi; Yamada, Noboru; Niihara, Koichi; Nakayama, Tadachika
Abstract: The energy‐harvesting ability of the lead‐free ferroelectric Ba(Zr, Ti)O3 was investigated and greatly enhanced using the Kim novel electrothermodynamic cycle for low‐temperature application. Ba(Zr, Ti)O3 was synthesized with a Zr:Ti ratio of 10:90 (BZT10) by hot‐press sintering, which exhibited a mix relaxor‐ferroelectric behavior. For power generation using the Kim cycle with low and high temperatures of TL = 25°C, TH = 120°C, the most optimized temperature pattern occurred for a heating time of 12.5 s and a cooling time of 22.5 s. Under these conditions, the electric field increased during the novel isodisplacement process, and the displacement variation in the isoelectric step reached the highest value and maximized the BZT10 cycle loop area. Applying these conditions while lowering TL to 20°C, an energy density ND = 504 mJ/cm 3 was achieved. This value is the highest obtained energy density in a practical test for lead‐free ferroelectric bulk material in the BaTiO3 family.